2016
DOI: 10.1111/zph.12323
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Campylobacter spp. from Client‐Owned Dogs and Cats, and Retail Raw Meat Pet Food in the Manawatu, New Zealand

Abstract: Campylobacter causes acute gastroenteritis in people worldwide and is frequently isolated from food, animals and the environment. The disease is predominately food-borne but many routes of transmission and sources of infection have been described, including contact with pets. The prevalence of Campylobacter spp. in dogs and cats varies widely, and data on New Zealand pets are limited. This study aimed to investigate the prevalence of Campylobacter spp. in dogs, cats and retail raw meat pet food products in New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 72 publications
8
60
1
2
Order By: Relevance
“…However, the sensitivity of the organism to drying, freezing and oxygen, plus relatively insensitive bacteriological detection methods, means that its apparent absence from prepared foods is perhaps not surprising. In contrast, Bojanic et al () isolated Campylobacter jejuni from 22% of raw retail pet foods in New Zealand. In the same study, univariable analysis showed an association between Campylobacter upsaliensis ‐positive rectal swabs and wet (but not specifically raw) feeding among both dogs and cats.…”
Section: Risks Of Raw Feedingmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the sensitivity of the organism to drying, freezing and oxygen, plus relatively insensitive bacteriological detection methods, means that its apparent absence from prepared foods is perhaps not surprising. In contrast, Bojanic et al () isolated Campylobacter jejuni from 22% of raw retail pet foods in New Zealand. In the same study, univariable analysis showed an association between Campylobacter upsaliensis ‐positive rectal swabs and wet (but not specifically raw) feeding among both dogs and cats.…”
Section: Risks Of Raw Feedingmentioning
confidence: 97%
“…This, combined with the presence of certain pathogens or antimicrobial‐resistant bacteria (summarised in Table ), poses risks of colonisation and disease for owners and pets alike. It has been noted by researchers sampling raw pet foods from commercial outlets that package warnings about preparation and hygienic handling of these pet foods are commonly absent (Finley et al , Strohmeyer et al , Mehlenbacher et al , Bojanic et al , van Bree et al ) and that packaging may be defective and leaky (Bojanic et al ).…”
Section: Risks Of Raw Feedingmentioning
confidence: 99%
“…2015; Bojanić et al . 2017). However, the isolation rates from faeces differ greatly depending on age, clinical signs, environment, concomitant diseases, infections with other enteropathogenic organisms, respective Campylobacter species, isolation method and design of the study (Torre & Tello 1993; Engvall et al .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs occur more commonly in puppies vs. adult dogs, and these may include diarrhoea, lethargy, anorexia, and occasionally fever and vomiting (Acke, 2018;Marks, Rankin, Byrne, & Weese, 2011). Dogs can also serve as reservoirs of additional species, mainly Campylobacter upsaliensis, Campylobacter helveticus, and Campylobacter lari (Bojanic et al, 2017;Giacomelli, Follador, Coppola, Martini, & Piccirillo, 2015;Holmberg, Rosendal, Engvall, Ohlson, & Lindberg, 2015). The prevalence of Campylobacter shedding in canines is variable, ranging from approximately 22%-43% for household pets (Acke et al, 2009;Leonard et al, 2011;Parsons et al, 2010;Procter et al, 2014) to 50%-73% for animals in shelters or kennels (Acke et al, 2006;Parsons et al, 2011).…”
mentioning
confidence: 99%